Long-Term Failure Rates of Interval Filshie Clips As a Method of Permanent Contraception - Kimberly A. Walhof; Lori M. Gawron; David K. Turok; Jessica N. Sanders (Mary Ann Liebert, 2021)
Background: In 1996, the U.S. Collaborative Review of Sterilization (CREST) reported permanent contraception failure rates by method, but did not include the Filshie clip. Subsequent research provides data for Filshie clip failure rates up to 24 months, but rigorously designed and executed studies examining failure rates beyond 2 years are lacking. Objectives: To describe non-Filshie and Filshie procedures, identify failures, and calculate 10-year pregnancy rates among patients who have undergone interval permanent contraception procedures with Filshie clips. Study Design: We performed chart review for patients who underwent interval permanent contraception procedures between 2000 and 2014 at our institution. We identified births after permanent contraception by utilizing both chart review and the Utah Population Database. We report results from life table analysis, with censoring at failure, 49 years of age, or last observed date of service. Results: In this cohort of 693 patients, surgeons most commonly used Filshie clips for interval permanent contraception (N?=?547, 78.8%). We classified pregnancies after Filshie clip procedures as verified (n?=?4) or self-reported (n?=?3). We obtained 5 years of data for 411 patients (59.3% of all permanent contraception procedures), and more than 10 years of data for 257 patients (37.1%). We calculated a cumulative 5- and 10-year pregnancy rate to be the same, including both verified and self-reported pregnancies, of 9.8 (95% confidence interval [CI] 4.1?23.3)/1000 women using Filshie clips. The 10-year rate of verified pregnancy is 2.8 (95% CI 1.0?15.7)/1000 women. Conclusion: Overall, long-term failure of Filshie clip interval permanent contraception procedures is infrequent, with a 10-year cumulative probability of failure of 4.1?23.3/1000 procedures performed. Filshie clips compare favorably with other methods of permanent contraception included in the CREST study, where the 10-year cumulative probability of failure ranged from 7.5 to 36.5/1000 procedures performed.